2009
DOI: 10.1080/1612197x.2009.9671922
|View full text |Cite
|
Sign up to set email alerts
|

Construct validity of multiple achievement goals: A multitrait‐multimethod approach

Abstract: Motivation-related issues have been one of the most popular topics in sport and exercise psychology research (Roberts, 2001). Over the past several decades, achievement goal frameworks have provided one of the main models laying the groundwork for the study of motivational processes in the physical domain. Differences in how people interpret and respond to their achievement-related activities have been found to be dependent on the achievement goal(s) emphasized. Nicholls (1984Nicholls ( , 1989, in particular, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…However, far fewer studies have focused on these links with regard to other-based (as opposed to task- or self-based) expectancies (Senko & Hulleman, 2013) that are most comparable to the performance expectancy construct focused on in the present research, and these studies have yielded mixed results (especially those conducted in the physical education or sport domain domain). Specifically, these studies have found performance expectancy to positively predict performance-approach goals, but they have only occasionally found it to negatively predict performance-avoidance goals (Cury, Da Fonsèca, Rufo, & Sarrazin, 2002; Ommundsen, 2004) and more often found performance expectancy and performance-avoidance goals to be unrelated (Jaakkola, Ntoumanis, & Liukkonen, 2016; Morris & Kavussanu, 2008; Nien & Duda, 2009) or even positively related (Wang, Biddle, & Elliot, 2007; Warburton & Spray, 2008; Zourbanos, Papaioannou, Argyropoulou, & Hatzigeorgiadis, 2014).…”
Section: Social Comparison Information Performance Expectancy and Per...mentioning
confidence: 99%
“…However, far fewer studies have focused on these links with regard to other-based (as opposed to task- or self-based) expectancies (Senko & Hulleman, 2013) that are most comparable to the performance expectancy construct focused on in the present research, and these studies have yielded mixed results (especially those conducted in the physical education or sport domain domain). Specifically, these studies have found performance expectancy to positively predict performance-approach goals, but they have only occasionally found it to negatively predict performance-avoidance goals (Cury, Da Fonsèca, Rufo, & Sarrazin, 2002; Ommundsen, 2004) and more often found performance expectancy and performance-avoidance goals to be unrelated (Jaakkola, Ntoumanis, & Liukkonen, 2016; Morris & Kavussanu, 2008; Nien & Duda, 2009) or even positively related (Wang, Biddle, & Elliot, 2007; Warburton & Spray, 2008; Zourbanos, Papaioannou, Argyropoulou, & Hatzigeorgiadis, 2014).…”
Section: Social Comparison Information Performance Expectancy and Per...mentioning
confidence: 99%
“…Established, assimilated and inherent served as the greater independent types of motivation and were equated with a numerous positive impacts. For people who were more independent in adapting their comportment, it was more likely that they would endure task engagement instead of ego engagement (Ryan and Deci, 2000), inherent goals and purposes (Sheldon et al , 2004), accessing rather than preventing mentality (Nien and Duda, 2009) and also more enjoyment recurrence (Deci and Ryan, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%